Cultivo integrado de juvenis de Tilápia do Nilo (Oreochromis niloticus) com a microalga Spirulina platensis: uma alternativa para tratamento de efluente aquícola - Coelho, Anderson Alan da Cruz (2012)
The environmental potential impacts from intensive aquaculture have increased public concern about the sustainability of the activity itself. The present work aimed to evaluate the zootécincos parameters of Nile tilapia , water quality, algal biomass production and rate of nitrogen removal compounds by Spirulina platensis realize an integrated cultivation of Nile tilapia (Oreocrhomis niloticus) with Spirulina platensis in a closed system of water circulation. The experiment took place at the Biotechnology Aquaculture Applied Center (CEBIAQUA) of The Fishing Engineering Department of the Federal University of Ceará. Tilapias culture was conducted in three treatments with four replicates at densities of 010, 0,15 and 0,20 juveniles L-1. The tilapias were fed ad libitum with a commercial ration (0,8 mm) containing 55% crude protein (CP), administered daily at 9, 13 and 17 h. For Spirulina platensis culture, initially, the inoculum was cultivated in an alternative chemical medium and later adapted to the Nile tilapia effluent and inoculated into 12 polyethylene basins. Throughout the experiment, the water of fishes boxes and of the respective microalgae basins was reused in the closed recirculation system between the two cultures, with only replacement of water due to evaporation. After the full development of S. platensis in the basins, the microalgae was collected using a 60 µm screen. The pH, temperature, dissolved oxygen, and levels of N-ammonia, N-nitrate and N-nitrite were also monitored during all the experimental period. The results showed that the most efficient stocking density was 0,10 L-1, because despite having the same final biomass of the other treatments it presented the lowest feed conversion ratio. The microalgae S. platensis was easily adapted and developed very well in the Nile tilapia’s effluent, regardless of fishes stocking density. With respect to water quality, it was evident that the cultures integration maintained the levels of N-ammonia (0,26 ± 0,03 mg L-1), N-nitrates (2,55 ± 0,71 mg L-1) and N- nitrites (0,19 ± 0,01 mg L-1) within acceptable values for the Nile tilapia culture.